Ginsenosides Rh2 and Rg3 exert their anti-cancer effects on non-small cell lung cancer by regulating cell autophagy and choline-phosphatidylcholine metabolism - Min, Zhao; Er-Xi, Che; Lin-Juan, Wang; Lin, Wang; Bi-Li, Liu; Qiu-Fang, Chen (Frontiers in Pharmacology, 2025)
BackgroundGinseng (Panax ginseng C. A. Meyer) herb itself and its derived preparations (e.g. Shenmai injection) are often prescribed for cancer patients as Traditional Chinese Medicines clinically in China. Ginsenosides Rh2 and Rg3 are two of main active components of ginseng. They have significant cytotoxic effect against non-small cell lung cancer (NSCLC), but the mechanisms are not very clear, especially lack of research on the combination of cell autophagy and metabolism.MethodsIn this study, we investigated the regulatory effects of ginsenosides Rh2 and Rg3 on cellular autophagy and metabolism in non-small cell lung cancer cell lines. Their regulations of cellular autophagy were detected by immunofluorescence, MDC staining, and transmission electron microscopy, while their regulations of cellular metabolism were detected by cellular metabolomics.ResultsOur results showed that ginsenosides Rh2 and Rg3 can significantly induce cell autophagy, and can lead to autophagic cell death through endoplasmic reticulum stress-autophagy axis, similar to ginseng total ginsenosides extract (TGS). They also significantly regulate the cell metabolome at the same time. The regulatory effect of ginsenosides Rh2 and Rg3 on the metabolism of choline-phosphatidylcholine may be the cellular metabolic mechanism of their cytotoxicity. Our findings suggested that ginsenosides Rh2 and Rg3 could induce autophagic cell death and regulate choline-phosphatidylcholine metabolism in NSCLC cells.ConclusionThis study has a new understanding of the antitumor mechanism of ginsenosides Rh2 and Rg3, and suggests a new direction of studying the pharmacological mechanism of natural active components.